Land Accumulation Dynamics in Developing Country Agriculture - Heath Henderson; Leonardo Corral; Eric Simning; Paul Winters (Inter-American Development Bank (IDB), 2014)
Understanding land accumulation dynamics is relevant for policy makers interested in the economic effects of land inequality in developing country agriculture. We thus explore and simultaneously test the leading theories of microlevel land accumulation dynamics using unique panel data from Paraguay. The results suggest that farm growth varies systematically with farm size –a formal rejection of stochasticgrowth theories (that is, Gibrat's Law)– and that titled land area may have considerable infuence on land accumulation. Furthermore, our estimates indicate that a dualistic agrarian structure is the likely product of the unfettered operation of land markets.
hdl:11319/6560
Keywords: C23; O13; O54; Q15; 330; Dynamic panel models; land accumulation; land inequality; Paraguay